2016
DOI: 10.1159/000445030
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Obstructive Pulmonary Disease and Cardiac Repolarization: Data from a Randomized Controlled Trial

Abstract: Background: Altered cardiac repolarization is a risk factor for sudden cardiac death and seems to be increased in chronic obstructive pulmonary disease (COPD) patients. Objective: Lung volume reduction surgery (LVRS) has been shown to improve breathing mechanics and lung function in patients with severe COPD and emphysema and possibly also improve altered cardiac repolarization. Methods: Thirty patients scheduled for LVRS were randomized to LVRS or to the control group. We investigated the treatment effect 3 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…Thus, the increased risk of mortality F I G U R E 1 An example of the calculation of frontal QRS-T angle using the automatic report of the ECG device as a result of cardiovascular causes in these patients has been principally attributed to cardiac arrhythmias and SCD because of the altered cardiac repolarization and depolarization. [2][3][4][5]16 Although the main mechanism of the altered cardiac repolarization and depolarization in patients with COPD has not been clearly elucidated, it has been suggested that hypoxemia, autonomic dysfunction and acidbase disturbances might be the potential causes. 6,8,17 Alteration in myocardial repolarization represents an increased risk for malign cardiac arrhythmia and SCD.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the increased risk of mortality F I G U R E 1 An example of the calculation of frontal QRS-T angle using the automatic report of the ECG device as a result of cardiovascular causes in these patients has been principally attributed to cardiac arrhythmias and SCD because of the altered cardiac repolarization and depolarization. [2][3][4][5]16 Although the main mechanism of the altered cardiac repolarization and depolarization in patients with COPD has not been clearly elucidated, it has been suggested that hypoxemia, autonomic dysfunction and acidbase disturbances might be the potential causes. 6,8,17 Alteration in myocardial repolarization represents an increased risk for malign cardiac arrhythmia and SCD.…”
Section: Discussionmentioning
confidence: 99%
“…In nearly 75% of patients with paroxysmal, AF has an increased duration of the initial portion of P wave in lead III [24]. Various investigations have reported the clinical value of P-wave measurements in the prediction of AF ( Table 2) [22,23,[25][26][27][28][29][30].…”
Section: Biphasic P Wavementioning
confidence: 99%
“…Hyperthyroidism [25,26] Postcardiac surgery [27,28] Renal failure and renal replacement therapy [22,23] Pulmonary diseases [29,30]…”
Section: Underlying Clinical Condition Referencesmentioning
confidence: 99%